The Effect of Different Branch Angles and Different Branch Pipe Sizes on the Onset Law of Liquid Entrainment - Li, Xiaoyu; Shen, Geyu; Liu, Ping; Gao, Jinchen; Gu, Ningxin; Meng, Zhaoming (Frontiers in Energy Research, 2020)
The T-junction has been extensively employed in nuclear power plant systems. To ensure the normal operation of nuclear power plant, the onset point of T-junction liquid entrainment requires in-depth studies. Existing studies have been conducted on the onset point of liquid entrainment, whereas most of them are for small branch pipes. This study primarily discussed the onset law of large branch pipe. Moreover, the effects of branch angle and size on the onset point of liquid entrainment were analyzed by comparing it with other branch pipe sizes in this study. This study demonstrated that the effect of branch angle on the onset point of entrainment complies with that of other sizes, i.e., because that the decrease in the inertial force in the vertical direction acting on the liquid phase by the gas phase with the decrease in the angle, hence, the onset requires larger Frg under the identical hbwith the decrease in the angle between the branch pipe and the horizontal direction. Moreover, by comparing the onset point law of liquid entrainment exhibiting different branch pipe sizes, the effect of branch pipe size on the onset was reported in this study that the smaller branch pipe requires the greater gas velocity in the presence of onset. We found that there is different flow resistance of different sizes of branch pipe, small branch has larger flow resistance, in order to remedy the flow resistance, the gas dynamic head decreases, thereby causing the Bernoulli effect weaker; the onset of liquid entrainment requires larger V3g.